1997
DOI: 10.1074/jbc.272.7.4474
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of qTBP42, a New Single-stranded and Quadruplex Telomeric DNA-binding Protein from Rat Hepatocytes

Abstract: Telomeres, the DNA-protein structures at the end of linear eukaryotic chromosomes, form protective caps that shield chromosome termini against degradative processes or fusion with other chromosome ends (1-4). The evolutionarily conserved nucleotide sequence of telomeric DNA consists of short nucleotide sequences repeated in tandem. All vertebrates, slime molds, filamentous fungi, and Trypanosoma have a repeated 5Ј-d(TTAGGG)-3Ј sequence of the telomeric strand oriented 5Ј to 3Ј toward the chromosome terminus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
54
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 62 publications
2
54
0
Order By: Relevance
“…The hnRNP-related proteins qTBP42 and uqTBP25 tightly bind and stabilize single-stranded and tetraplex telomeric sequences (37,39). However, a survey of the interaction of qTBP42 and uqTBP25 with tetraplex structures of different DNA sequences revealed that neither protein detectably bound d(CGG) n tetrahelices.…”
Section: Bimolecular Tetraplex Forms Of D(cgg) N But Not Of a Telomermentioning
confidence: 99%
See 2 more Smart Citations
“…The hnRNP-related proteins qTBP42 and uqTBP25 tightly bind and stabilize single-stranded and tetraplex telomeric sequences (37,39). However, a survey of the interaction of qTBP42 and uqTBP25 with tetraplex structures of different DNA sequences revealed that neither protein detectably bound d(CGG) n tetrahelices.…”
Section: Bimolecular Tetraplex Forms Of D(cgg) N But Not Of a Telomermentioning
confidence: 99%
“…Previously identified as proteins that tightly bind and stabilize quadruplex telomeric DNA (37)(38)(39), it is shown here that qTBP42 and uqTBP25 destabilized bimolecular tetraplex structures of d(CGG) n without detectably binding these tetrahelices. Destabilization of tetraplex d(CGG) n by either protein did not require ATP or Mg 2ϩ or the presence of an unpaired single-strand tail at the ends of the tetrahelix.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, a protein from Trypanosoma, ST-1, binds to the telomeric double-stranded repeat as well as to its singlestranded C-rich component [14]. In vertebrates, the nuclear protein from rat hepatocytes, qTBP42, has been shown to recognize each of the single-stranded forms of the telomeric repeat [9]. Several proteins that interact with polypyrimidine ssDNA have been described.…”
mentioning
confidence: 99%
“…Another group of proteins, ST-2 from Trypanosoma [8], qTBP42 from rat [9], human replication factor C [10], and murine STBP [11] and A1/UP1 [12], also bind to the single-stranded G-rich telomeric motif, although their function has not been fully ascertained. The last of these, however, is the first ssDNA-binding protein shown to be directly involved in mammalian telomere biogenesis, suggesting a possible mechanism by which telomere length can be modulated [13].…”
mentioning
confidence: 99%